XIVModern Literature. Issue 1 (8th November 2022) - Ross, Shawna; Mourant, Chris; Fischer, Tiana M; Phillips, Joshua; Parsons, Katherine; Stringfellow, Sophie; RodrÍguez MartÍn, Gustavo A; Saunders, Graham; Richards, Joshua; Quin, Jack
Abstract: This chapter has eight sections 1. General. 2. Fiction Pre-1945; 3. Fiction Post-1945; 4. Drama Pre-1950; 5. Drama Post-1950; 6. British Poetry Pre-1950; 7. British Poetry Post-1950; 8. Modern Irish Poetry. Section 1 is by Shawna Ross; section 2(a) is by Chris Mourant; section 2(b) will resume in 2023; section 2(c) is by Tiana M. Fischer; section 2(d) will resume in 2023; section 2(e) is by Joshua Phillips; section 3(a) is by Katherine Parsons; section 3(b) will resume in 2023; section 4(a) is by Sophie Stringfellow; section 4(b) is by Gustavo A. Rodríguez Martín; section 5 is by Graham Saunders; section 6(a) will resume in 2023, section 6(b) is by Joshua Richards; section 7 will resume in 2023; section 8 is by Jack Quin.